Fragile eternity - Marr, Melissa (New York : Bowen Press, 2009)
Aislinn and Seth struggle with the unforeseen consequences of Aislinn's transformation from mortal girl to faery queen as the world teeters on the brink of cataclysmic violence.
Sequel to: Wicked lovely.
Sequel: Radiant shadows.
Keywords: Fairies -- Juvenile fiction; Fantasy fiction; Young adult fiction; Fantasy fiction